Interpreting the Social Order for the Moral Personality Upbringing in the Context of the New Educational Standards. - O. A. Teplyakova (Образование и наука)
The author makes an attempt to interpret the social order for upbringing the spiritually and morally developed personality in the light of the new state educational standards. Such a necessity is caused by globalization processes, technogenic civilization developments, ecological challenges, contradictions and conflicts of people with opposing views representing different cultures and religious denominations. The author emphasizes the continuity and interrelations between the new challenges and classical ideas of Russian pedagogy, as well as the new trends in moral education developments. Analyzing the approximate curricula of the primary and secondary education, the author demonstrates the mechanisms for setting the socially acceptable behavior patterns and developing the spiritually and morally advanced personality.